The relationship between knowledge management and leadership: mapping the field and providing future research avenues - Pellegrini, Massimiliano Matteo; Ciampi, Francesco; Marzi, Giacomo; Orlando, Beatrice (Journal of knowledge management, 2020)
Purpose Effectively handling knowledge is crucial for any organization to survive and prosper in the turbulent environments of the modern era. Leadership is a central element for knowledge creation, acquisition, utilization and integration processes. Based on these considerations, this study aims to offer an overview of the evolution of the literature regarding the knowledge management-leadership relationship published over the past 20 years. Design/methodology/approach A bibliometric analysis coupled with a systematic literature review were performed over a data set of 488 peer-reviewed articles published from 1990 to 2018. Findings The authors discovered the existence of four well-polarized clusters with the following thematic focusses: human and relational aspects, systematic and performance aspects, contextual and contingent aspects and cultural and learning aspects. The authors then investigated each thematic cluster by reviewing the most relevant contributions within them. Research limitations/implications Based on the bibliometric analysis and the systematic literature review, the authors developed an interpretative framework aimed at uncovering several promising and little explored research areas, thus suggesting an agenda for future knowledge management-leadership research. Some steps of the paper selection process may have been biased by the interpretation of the researcher. The authors addressed this concern by performing a multiple human subject reading process whose reliability was confirmed by a Krippendorf’s alpha coefficient value >0.80. Originality/value To the best knowledge, this is the first study to map, systematize and discuss the literature concerned to the topic of the knowledge management-leadership relationship.